AB1117 Isolated cervical arthritis as the sole manifestation of familial mediterranean fever: a case report. (12th June 2018) - Dagher, R.; Samarani, M.; Chelala, A.; Fadous Khalife, M.C.
Abstract : Background: Familial Mediterranean Fever (FMF) is an autosomal recessive disease affecting mainly eastern Mediterranean populations. Fever and Abdominal pain are the 2 most prevalent features. The most common arthritic manifestation of FMF is acute self-limiting monoarthritis. 5% of FMF patients develop chronic erosive arthritis. FMF mutation M694V has been associated to an increased risk of spondylarthropathy. Objectives: We report the case of a child with cervical spine inflammation as the sole presentation of FMF. Methods: A boy born to non-consanguineous parents presented at the age of 4 with complete blockage of his neck. He was described to have experienced progressive neck stiffness since the age of 3 years. His history is notable for intermittent limp at the age of 1 with complete spontaneous remission, and possible recurrent fever in the first 2 years of life. Family history is negative. His physical exam revealed a painful and completely blocked neck in all movements, and stubby fingers. He had failure to thrive and a big belly without hepatosplenomegaly. Cognitive development was normal. Laboratory tests revealed increased inflammatory markers. Other biological tests were insignificant. ANA, RF, anti-CCP and HLA B27 were negative. Lysosomal enzyme activities were normal ruling out muccopolysacharidosis, mucolipidoses and multiple sulfatase deficiencies. Work-up for failure to thrive was noncontributory. Ophtalmic screening showed no abnormalities. Cervical spine plain radiographs were normal. Cervical MRI showed global contrast enhancement of cervical vertebrae and joints with blurring of the osseous contours and synovial inflammation; bone oedema was noted and involved some posterior arcs, spinous processes and pedicules. Sacro-iliac MRI was normal. The child was treated with oral steroids along with methotrexate and etanercept secondarily due to steroid dependance. Inflammatory markers normalised and clinical improvement was noted as the range of motion of neck increased and pain subsided. Repeated MRI after 6 months showed an almost normal image. Results: Given this atypical isolated inflammation of the cervical spine, genetic testing for FMF was conducted. We identified 2 typical mutations (M694V and M694I) confirming the diagnosis of FMF. Colchicine treatment was started. Conclusions: To the best of our knowledge, this is the first report of FMF masquerading as neck arthritis. Early spondylarthropathy is a possibility, but this unusual neck inflammation might be an isolated arthritis associated to FMF. Based on this clinical presentation, in the setting of atypical arthritis, diagnosis of FMF is to be raised in at-risk ethnicities, even in the absence of familial history and common clinical signs. References: [1] Sönmez HE, Batu ED, Demir S, Bilginer Y, Özen S. Comparison of patients with familial Mediterranean fever accompanied with sacroiliitis and patients with juvenile spondyloarthropathy. Clinical and Experimental Rheumatology. 2017Nov-Dec;35 Suppl 108(6):124–127 [2] Younes M, Kahn MF, Meyer O. Hip involvement in patients with familial Mediterranean fever. A review of ten cases. Joint Bone Spine. 2002Dec;69(6):560–5. [3] Güncan S, Bilge NŞY, Cansu DÜ, Kaşifoğlu T, Korkmaz C. The role of MEFV mutations in the concurrent disorders observed in patients with familial Mediterranean fever. European Journal of Rheumatology. 2016;3(3):118–121. Disclosure of Interest: None declared